Acute necrotising pancreatitis in a pediatric patient with pseudocysts and portal vein thrombosis: A rare case report - Muhammad Umair; Rameez, Roshna; Hassan, Faiqa (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Acute necrotising pancreatitis (ANP) is a severe and rare form of acute pancreatitis (AP) in children. It can present with complications like pancreatic pseudocysts and vascular thrombosis which significantly increase chances of morbidity in patients and require a comprehensive diagnostic and therapeutic approach. We report the case of a 3-year-old male presenting with abdominal pain, vomiting and fever. Radiological imaging revealed findings consistent with acute on chronic necrotizing pancreatitis complicated by multiple intra- and peripancreatic pseudocysts with partial portal vein thrombosis. The patient was conservatively managed with intravenous fluids, antibiotics, anticoagulation and nutritional support. This case highlights the significance of considering severe pancreatic pathology in pediatric patients who present with non-specific abdominal complaints and emphasises the critical role of imaging and multidisciplinary care in improving clinical outcomes.